Pengaruh Strategi Brain Based Learning dengan Media Ular Tangga Terhadap Hasil Belajar Siswa di SMP Swasta al-Ulum - Seby Anjella; Husnarika Febriani; Lailatun Nur Kamalia Siregar (Mu'allim, 2023)
This article aims to determine the effect of learning with strategiesBrain Based Learning with the help of snakes and ladders media on student learning outcomes at Al-Ulum Private Middle School Medan. This study uses a Quasi Experiment type of research. The population in this study were students of class VIII. The sample used in this study was class VIII 4 as the experimental class. And VIII 5 as the control class. Each class consists of 29 students. The instrument in this study was a multiple choice test consisting of 30 items. Data analysis of student learning outcomes using the test formulattest, also with the help of SPSS Version 22 data processing. Data analysis of student learning outcomes by calculating the average value obtained shows that the experimental class is higher than the control class. The prerequisite test proves that the data obtained is normally distributed and homogeneous. Test calculation resultsttest Sig value is obtained. (2-tailed) of 0.000 <0.05. Testttest experimental class and control class have been obtainedtcount worth 14,855 andttableworth 1,697, so it showstcount > ttable. The conclusion in this study explains that there is an influence on student learning outcomes on the respiratory system material at Al-ulum Private Middle School, after implementing the learning strategyBrain Based Learning by means of snakes and ladders.